Pengaruh Efikasi Diri, Pendidikan Kewirausahaan, Motivasi Berwirausaha Terhadap Minat Berwirausaha Siswa - Ayu Anggraini Putri; Syamwil Syamwil (Jurnal Ecogen, 2021)
This study aims to identify (1) the effect of self efficacy, entrepreneurship education, entrepreneurship motivation towards student’s entrepreneurship interest (2) the influence of self efficacy towards student’s entrepreneurship interest (3) the impact of entrepreneurship education to student’s entrepreneurship interest (4) the effect of entrepreneurship motivation against student’s entrepreneurship interest. This study was conducted on students of XI class in SMK Negeri 2 Padang. The type of this study was descriptive quantitative. The population of this study were 452 students of XI class in SMK Negeri 2 Padang. Accidental Sampling technique was used in collecting the sample with 104 students. The data was primary data which collected using questionnaire. This study was used validity and reliability in data testing. In analyzing data, this study was used descriptive analysis, prerequisite test, multiple regression, simultaneous significance test (F Test), and determinant coefficient (R2) and T test. The analysis of data in this study was used SPSS version 16. The result showed (1) self efficacy, entrepreneurship education, entrepreneurship motivation have significant effect on student’s entrepreneurship interest of XI class in SMK Negeri 2 Padang, seen from sig 0,000 < 0,05 (2) self efficacy has significant influence on student’s entrepreneurship interest of XI class in SMK Negeri 2 Padang, it can be observed from sig 0,000 < 0,05 (3) entrepreneurship education has significant impact on student’s entrepreneurship interest of XI class in SMK Negeri 2 Padang, seen from sig 0,000 < 0,05 (4) entrepreneurship motivation has significant effect on students entrepreneurship interest of XI class in SMK Negeri 2 Padang, seen from sig 0,000 < 0,05.Keywords : self efficacy, entrepreneurship education and entrepreneurship motivation